Bug as a Drug. Lytta vesicatoria L. Applications in Nineteenth Century Official Medicine - Smakosz, Aleksander Karol (Pharmacognosy Reviews)
Nowadays the limited number of animal species are used in official medicine. For example, equine urine is a source of conjugated oestrogens used in menopausal hormone therapy; porcine intestine is the only approved source of anticoagulant and antithrombotic drug— enoxaparin. Until the end of nineteenth century animal-based medicines were very popular. Raw materials included substances obtained from mammals, birds, reptiles, and insects were used. Among insects the most important were red wood ant (Formica rufa L.), cochineal (Dactylopius coccus Costa), western honeybee (Apis mellifica L.) and cantharides (Lytta vesicatoria L.). Initially this species was only gathered in Spain. Because of that, this beetle was called Musca hispanica (spanish fly). In subsequent years it was found in other European countries such as France, Italy, Germany, Hungary, Poland, and Great Britain. In my research I have analyzed six European state pharmacopoeias published in nineteenth century—Pharmacopoea Regni Poloniae (1817), Pharmacopoea Fennica (1819), Pharmacopea Bavarica (1822), Pharmacopea Norvegica (1854), Pharmacopea Belgica (1854) and British Pharmacopoeia (1867). A total of 18 pharmaceutical preparations were noted. Among the analyzed sources, the most frequently reported pharmaceutical preparations were plaster of cantharides (Emplastrum Cantharidum) and ointment of cantharides (Unguentum Cantharidum)—these medications were found in all pharmacopoeias. Less common were tincture of cantharides (Tinctura Cantharidum), concentrated essence of cantharides (Essentia Cantharidum Fortior) and blistering paper (Charta epispatica) – they were presented in two works. Other drugs were reported individually. This study indicates the potential application of L. vesicatoria in contemporary medicine.
Keywords: Cantharides; Ethnopharmacology; History of Pharmacy; Spanish Fly; Pharmacopoeia; Dosage forms